2020
DOI: 10.1177/0961203319897139
|View full text |Cite
|
Sign up to set email alerts
|

Mobile health technologies for the management of systemic lupus erythematosus: a systematic review

Abstract: Objective We aimed to perform a standardized review of available mobile health (mHealth) applications (apps) for systemic lupus erythematosus (SLE) and to conduct a systematic review of the literature on mHealth technologies in SLE. Methods Google Play and AppStore in the United States of America were queried and the quality of eligible mHealth apps was assessed using the Mobile App Rating Scale (MARS). Web of Science, EMBASE, Medline, and Cochrane databases were systematically searched from inception through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 44 publications
1
41
0
Order By: Relevance
“…A five-point Likert questionnaire was designed after reviewing the relevant studies conducted on self-care against COVID-19 or its management [3,13,[21][22][23][24][25] and investigating the websites of the WHO, the International OCD Foundation, and the Centres for Disease Control and Prevention (CDC) [26][27][28]. e questionnaire was designed to determine the required information and features for developing the application and helped collect the opinions of obstetricians and pregnant women about the significance of these needs.…”
Section: Methodsmentioning
confidence: 99%
“…A five-point Likert questionnaire was designed after reviewing the relevant studies conducted on self-care against COVID-19 or its management [3,13,[21][22][23][24][25] and investigating the websites of the WHO, the International OCD Foundation, and the Centres for Disease Control and Prevention (CDC) [26][27][28]. e questionnaire was designed to determine the required information and features for developing the application and helped collect the opinions of obstetricians and pregnant women about the significance of these needs.…”
Section: Methodsmentioning
confidence: 99%
“…The percentage of drug adherence using web-based education with social media intervention improved significantly from 50 to 92% [ 182 ]. A recent systematic review study assessed mobile health technologies to support the management of cSLE and adult SLE, and it demonstrated that currently available instruments were of poor quality and limited functionality [ 183 ].…”
Section: Drug Adherence For Adolescentsmentioning
confidence: 99%
“…In regard to SSc/SLE eHealth support, web-based resources are often of low quality, have inadequate readability and limited functionality. [9][10][11] Several studies demonstrate that patients with rare connective tissue diseases and their providers are interested in web-based education and support. [12][13][14] However, few online programmes focus on critical concepts of health equity, patient engagement and empowerment.…”
Section: Key Messagesmentioning
confidence: 99%